STRATEGIES TO IMPROVE THE QUALITY OF HUMAN RESOURCES IN THE KARANGANYAR PRIMARY TAX SERVICE OFFICE - Pratomo Riyadi; Supawi Pawenang; Sudarwati Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Human resources (HR) are an important asset for an organization to achieve a competitive advantage in the era of globalization. Efforts to develop the capacity of human resources for the apparatus have not been managed properly. This is shown, among others, by the difficulty in changing the way of mindset and working of the apparatus, low discipline and employee ethics, a career system that is not fully based on work performance, an inadequate remuneration system for a decent life, recruitment that has not been carried out based on the required educational qualifications , the implementation of education and training that has not been able to fully improve performance, weak supervision and audits of employee performance, and personnel management information systems that are not functioning optimally. Research objectives are (1) analyzing the strategy of increasing human resources for employees at the Karanganyar Primary Tax Office (2) analyzing the supporting and inhibiting factors for human resource improvement strategies at the Karanganyar Primary Tax Office. This type of research used qualitative research. The subjects in this study were employees of the Karanganyar Primary Tax Office. The data method used in this research is SWOT. The superior position of the Karanganyar Primary Tax Office by using a SWOT diagram showing the position of Human Resources in Quadrant I, a position that greatly uses existing opportunities to increase the strength of the agency. This means that the existing opportunities are used to further increase the strength of the human resources at Karanganyar Primary Tax Office. The focus of this strategy is to maximize opportunities to improve the quality of human resources. Keywords: SWOT, quality of human resources